Determination of Quality Characteristics of Kundhi Buffalo Bull Semen - Asmatullah Kaka; Akeel Ahmed Memon; Pershotam Khatri; Hamzo Khan Kumbhar; Dildar Hussain Kalhoro; Mansoor Tariq; Shoaib Ahmed Pirzado; Ahmed Nawaz Tunio (Journal of Basic & Applied Sciences, 2016)
The objective of present study was to investigate the quality characteristics of semen collected from kundhi bulls. Semen was collected by an artificial vagina and transported into laboratory immediately for evaluation. Total of 96 (Twenty four from each bull) semen the samples were evaluated and found creamy white. The mean (±SEM) were mass activity (+++), volume (2.25 ± 0.01 ml), pH (6.10 ± 0.007), progressive motility (69 ± 0.34%,) sperm concentration (1542 ± 9.20x106/ml), morphology (79 ± 1.37%) and sperm membrane (55.56 ± 1.37%) respectively. Non-significant (P>0.05) difference between the bulls for the characteristics except percentages morphology and sperm membrane where a significant (P<0.05) variation was found. It was concluded that the quality characteristics of khundi buffalo bull maintained standard score considered for freezing and cryopreservation and A.I programme.